Digital Technology Based Self-Management Interventions for Hypertension Management: A Literature Review - Hilda Harun (Journal of Epidemiology and Health Science, 2025)
Background: Hypertension is a major non-communicable disease and a leading cause of premature death worldwide. In the digital era, mobile health (mHealth) technology has become one of the commonly used solutions to provide education for hypertensive patients in managing the disease and to support self-management for patients with chronic conditions, particularly hypertension (HT). Objective: This study aims to examine the benefits and effects of digital technology in supporting the self-management of patients with hypertension. Method: The research method used is a non-systematic literature review based on relevant sources related to the research topic, with literature reviewed from scientific articles (original research) selected by the researcher. Results: Based on studies conducted in several countries, there has been an improvement in the self-management of hypertensive patients, leading to better disease control such as medication adherence, behavioral changes for lifestyle modification (e.g., physical activity, DASH diet). Patients also reported that using digital technology for self-management was highly beneficial for controlling blood pressure (BP) and reducing both systolic blood pressure (SBP) and diastolic blood pressure (DBP). Conclusion: Digital technology-based interventions are highly beneficial and effective in enhancing the self-management of hypertension patients in managing HT and in lowering BP. Keywords: Intervention, Digital Technology, Self-Management, Hypertension